2020
DOI: 10.5152/tao.2020.5502
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Comorbid Diseases on Postoperative Complications in Children after Adenotonsillectomy: Is It a Myth?

Abstract: Owner and Responsible Manager on behalf of the Turkish Otorhinolaryngology Head and Neck Surgery Society / Türk Kulak Burun Boğaz ve Baş Boyun Cerrahisi Derneği adına Sahibi ve Sorumlu Yazı İşleri Müdürü: Özgür YİĞİT •

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Therefore, addressing the challenges associated with poor oral intake and inadequate pain control is crucial for minimizing bleeding risk and optimizing patient recovery following tonsillectomy. Despite advancements in tonsillectomy techniques, the persistence of poor oral intake has been highlighted in the study conducted by Demir et al 24 Additionally, a recent local study by Alsalamah et al 14 identified poor oral intake as a contributing cause to readmission following the procedure. However, the study by Rohlfing et al 25 did not find a significant association between poor oral intake and readmission.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, addressing the challenges associated with poor oral intake and inadequate pain control is crucial for minimizing bleeding risk and optimizing patient recovery following tonsillectomy. Despite advancements in tonsillectomy techniques, the persistence of poor oral intake has been highlighted in the study conducted by Demir et al 24 Additionally, a recent local study by Alsalamah et al 14 identified poor oral intake as a contributing cause to readmission following the procedure. However, the study by Rohlfing et al 25 did not find a significant association between poor oral intake and readmission.…”
Section: Discussionmentioning
confidence: 99%
“…However, OAHI parameters were not used in their study. 18 While there is no consensus as to whether each comorbidity alone contributes to postoperative risk, there may be an uninvestigated interplay between presence of comorbidity and very severe OSAS that may be more useful in predicting postoperative complications. Although our prior study did not show an association between OSAS severity and cardiopulmonary abnormalities, other comorbidities in patients with very severe OSAS, such as failure to thrive, trisomy 21, craniofacial abnormalities, pulmonary hypertension, and neuromuscular disease, have not yet been closely investigated.…”
Section: Discussionmentioning
confidence: 99%